PRELIMINARY EVALUATION OF THE INFLUENCE OF TREATMENT OF SEEDS OF RICE ON PENETRATION OF THE ROOTS BY ð˜”ð˜Œð˜“ð˜–ð˜ð˜‹ð˜–ð˜Žð˜ ð˜•ð˜Œ ð˜‘ð˜ˆð˜ð˜ˆð˜•ð˜ð˜Šð˜ˆ - Laughlin, C. W.; Lordello, Luiz Gonzaga E.; Orsi, Eujandir W. de Lima (REVISTA DE AGRICULTURA, 2020)
PRELIMINARY EVALUATION OF THE INFLUENCE OF TREATMENT OF SEEDS OF RICE ON PENETRATION OF THE ROOTS BY ð˜”ð˜Œð˜“ð˜–ð˜ð˜‹ð˜–ð˜Žð˜ ð˜•ð˜Œ ð˜‘ð˜ˆð˜ð˜ˆð˜•ð˜ð˜Šð˜ˆ